The Ethical Philosophic Dimension of Responsibility in Mitigating the COVID-19 Disaster in Indonesia - Nugroho, Sigit Sapto; Sarjiyati, Sarjiyati; Haryani, Anik Tri; Purwati, Yuni; Budiono, Arief; Kuswanto, Heru (Open Access Macedonian Journal of Medical Sciences, 2021)
The coronavirus disease (COVID-19) pandemic is a global disaster and every country makes efforts to mitigate it. There needs to be a gradual rise of awareness on the ethics of responsibility to others in the form of a sense of solidarity and togetherness. Philosopher Emmanuel Levinas stated that the basic facts in his philosophy were other people. Therefore, his philosophy is the ethics of responsibility toward others. COVID-19 deserves to be a momentum to reflect on Levinas’ philosophy, by reaffirming responsibility toward others as an ethical fact in mitigating the COVID-19 disaster in Indonesia.